A method for preparing a heat-stretchable modified LAGP glass and ceramic electrolyte fiber

CN118270988BActive Publication Date: 2026-10-20NANJING UNIV OF POSTS & TELECOMM
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410393213.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-02
Publication Date
2026-10-20
Estimated Expiration
2044-04-02

AI Technical Summary

Technical Problem

然而,LATP/LAGP玻璃的玻璃转变温度范围△T较低(LATP的△T<60℃,LAGP的△T<100℃),难以满足热拉丝的需求(△T>100℃,最好大于120℃)

Benefits of technology

[0021](1)本发明提供了一种可热拉伸改性LAGP玻璃,该LAGP玻璃热稳定性好,其玻璃化转变温度范围△T>100℃,可以通过热拉丝工艺制备成陶瓷电解质纤维。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118270988B_ABST
    Figure CN118270988B_ABST
Patent Text Reader

Abstract

The application discloses a heat-stretchable modified LAGP glass, which has a general structure of Li 1.5+x Al 0.5 Ge 1.5 P 3‑x Si x O 12 ·yM·zN, wherein M is a rare earth oxide, N is a flux, 0≤x≤0.5, 0≤y≤0.1, and 0≤z≤0.15. The heat-stretchable modified LAGP glass can be prepared by a melt quenching method at 1200-1300 DEG C, and has the advantages of good heat stability, a glass transition temperature range ΔT>100 DEG C, a fiber drawing temperature of 100-120 DEG C above a DSC temperature, a ceramic electrolyte fiber obtained through high-temperature crystallization treatment, low cost, simple operation, low temperature, short cycle, large output, adjustable fiber diameter, and a room-temperature ionic conductivity of the prepared ceramic electrolyte fiber reaching 10 ‑4 Scm ‑1 orders of magnitude or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing thermostretchable modified LAGP glass and ceramic electrolyte fibers, belonging to the field of energy materials. Background Technology

[0002] Solid electrolytes in all-solid-state lithium-ion batteries can fundamentally overcome the potential safety issues of organic electrolytes and inhibit the growth of surface dendrites on the lithium metal anode. They are widely recognized as an ideal choice for solving the energy density bottleneck and safety challenges of traditional lithium-ion batteries. Polymer solid electrolytes suffer from low room-temperature ionic conductivity, narrow electrochemical windows, and poor electrode material compatibility. Sulfides in inorganic solid electrolytes have high room-temperature ionic conductivity but are unstable to O2 and H2O. Oxides and phosphates offer high air stability and good ionic conductivity, but their thin-film formation, brittleness, and interface problems with the electrodes are difficult to overcome. In contrast, polymer composite solid electrolytes combine the advantages of polymer / ceramic solid electrolytes, making them a more ideal solid electrolyte material for solid-state lithium-ion batteries. In composite solid electrolytes containing active fillers (such as LLZO, LAGP, LATP, etc.), there are three ion transport channels: polymer phase, polymer / ceramic interface, and active ceramic phase. Moreover, the ion transport rate of polymer / ceramic interface and active ceramic phase is higher (Zhang ZY, Chen H, Liu ZL, et al. Front. Energy 2022, 16(5): 706–733, Ding Y, He B, Wang D, et al. Energy Mater. Adv. 2023;4: Article0041). Therefore, ceramic solid electrolyte fiberization is the most effective way to improve the film-forming properties and ion conduction capacity of composite solid electrolytes.

[0003] Currently, only a very few articles report on phosphate (such as LATP and LAGP) ceramic nanofibers (Lancel G, Stevens P, Toussaint G, et al. Langmuir 2017, 33, 9288-9297; Monaca AL, Girard G, Savoie S, et al. J. Mater. Chem. A, 2021, 9, 13688; Monaca AL, Girard G, Savoie S, et al. Nanoscale, 2022, 14, 5094). Among these existing technologies, LAGP nanofibers utilize high-cost soluble germanium salts (GeCl4) in large quantities, and the precursor solution needs to be prepared in an inert atmosphere glove box, resulting in extremely high costs. More importantly, the efficiency of electrospinning to prepare nanofibers is extremely low, severely hindering the development and application of LATP / LAGP nanofiber-based composite solid electrolytes. In contrast, the preparation of fibers and ceramic electrolytes from LATP / LAGP glass via thermal drawing is lower in cost and more efficient. However, the glass transition temperature range ΔT of LATP / LAGP glass is relatively low (ΔT < 60℃ for LATP, ΔT < 100℃ for LAGP), making it difficult to meet the requirements of hot drawing (ΔT > 100℃, preferably greater than 120℃). Currently, there is only one article reporting on LAGP glass fiber (He K, Xie P, Zu CK, et al. RSC Adv 2019, 9, 4157–4161), but it uses a high-temperature extrusion process, which involves high temperatures (1100℃), high risks, and high equipment requirements. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a heat-stretchable modified LAGP glass with a glass transition temperature range of ΔT > 100℃, which can be prepared into ceramic electrolyte fibers through a hot drawing process.

[0005] The present invention also aims to provide a method for preparing ceramic electrolyte fibers using the above-mentioned heat-stretchable modified LAGP glass. This method has low raw material cost, high preparation efficiency, and the prepared fibers have adjustable diameter and high ionic conductivity.

[0006] The objective of this invention can be achieved through the following technical solutions:

[0007] A thermostretchable modified LAGP glass having the following general structural formula:

[0008] Li 1.5+x Al 0.5 Ge 1.5 P 3-x Si x O 12·yM·zN,

[0009] Wherein, M is a rare earth oxide, selected from one or more of Y₂O₃, La₂O₃, Gd₂O₃, Nd₂O₃, Lu₂O₃, Yb₂O₃, Eu₂O₃, Tm₂O₃, Er₂O₃, Dy₂O₃, Ho₂O₃, Sm₂O₃, CeO₂, and Tb₄O₇. The introduction of the M component can not only improve the crystallization temperature and thermal stability of LAGP glass, but also enhance the ion conductivity of rare earth ions with low valence states and large ionic radii.

[0010] N is a fluxing agent, selected from one or more of Li2O, B2O3, LiF, Li3BO3, and H3BO3. The introduction of fluxing agents can appropriately reduce the glass melting temperature and glass transition temperature. Moreover, lithium-containing fluxing agents can increase the lithium content in LAGP, which helps to improve ionic conductivity.

[0011] The range of values ​​for x, y, and z is 0 ≤ x ≤ 0.5, 0 ≤ y ≤ 0.1, and 0 ≤ z ≤ 0.15.

[0012] Furthermore, the values ​​of x, y, and z are in the range of 0.2≤x≤0.4, 0.06≤y≤0.08, and 0.03≤z≤0.08.

[0013] In the thermostretchable modified LAGP glass of the present invention, the introduction of Si not only improves the thermal stability of the LAGP glass, but also... 4+ For P 5+ Partial substitution of ions increases Li + Ion coordination improves the electrical properties of NASICON structured glass-ceramics.

[0014] The above-mentioned method for preparing heat-stretchable modified LAGP glass is as follows: according to the proportions in the above general formula, weigh lithium source, aluminum source, phosphorus source, GeO2, SiO2, rare earth oxide, and flux and mix them evenly. Place the resulting mixture in a furnace at 1200-1300℃ and melt it for 10-60 minutes to obtain glass liquid. Then, cast the glass liquid into a mold to form it. After annealing, cool it to room temperature to obtain heat-stretchable modified LAGP glass.

[0015] Furthermore, the lithium source is at least one of Li2CO3, LiNO3, and LiPO3, the phosphorus source is at least one of P2O5, NH4H2PO4, (NH4)2HPO4, and LiPO3, and the aluminum source is at least one of Al2O3 and Al(PO3)3.

[0016] Furthermore, the annealing temperature is 400–500°C, and the time is 2–12 hours.

[0017] A method for preparing ceramic electrolyte fiber: The above-mentioned heat-stretchable modified LAGP glass is processed into preforms with a diameter of 2-20 mm through cutting, grinding and polishing processes. Then, it is placed in the drawing furnace of the optical fiber drawing tower and heated to 100-120°C above the glass Tg (glass transition temperature) at a rate of 2-5°C / min. The fiber diameter is controlled by adjusting the feeding speed and winding speed of the drawing tower. The fiber is obtained by hot drawing. The obtained fiber is heated to the range of glass Tc (crystallization temperature) ±20°C at a rate of 2-5°C / min and held for 10-120 min. Then, it is heated to 700-850°C and held for 30-120 min to obtain ceramic electrolyte fiber.

[0018] Furthermore, the fiber diameter is 50–1000 μm.

[0019] A method for testing the ionic conductivity of ceramic electrolyte fibers: A section of ceramic electrolyte fiber with a length of 2-5 mm is taken, and both ends are polished neatly. Then, an adhesive conductive material is used to adhere both ends to a conductive foil / film. The EIS spectrum is then measured using an electrochemical workstation. The ionic conductivity is calculated using the formula σ = L / R·S based on the end face area (S) and effective length (L) of the ceramic electrolyte fiber. The adhesive conductive material is at least one of conductive silver paste, conductive silicone, conductive adhesive, and conductive tape. The conductive foil / film is one of aluminum foil, copper foil, silver foil, tin foil, nickel foil, stainless steel foil, or carbon fiber film.

[0020] The beneficial effects of this invention are:

[0021] (1) The present invention provides a heat-stretchable modified LAGP glass with good thermal stability and a glass transition temperature range ΔT>100℃, which can be prepared into ceramic electrolyte fiber by hot drawing process.

[0022] (2) This invention uses processes such as melting and thermally stretchable modified LAGP glass, fiber drawing, and fiber crystallization to prepare ceramic electrolyte fibers. It has the advantages of simple operation, short cycle, large output, and adjustable fiber diameter. The prepared ceramic electrolyte fibers have a room temperature ionic conductivity of 10. -4 Scm -1 Above the scale.

[0023] (3) The present invention uses inexpensive germanium source GeO2 (unit price less than 20 yuan / g), which can significantly reduce costs compared with other expensive germanium sources used to prepare LAGP nanofibers (GeCl4 unit price greater than 110 yuan / g, tetraethyl germanium, tetramethyl germanium and tetrabutyl germanium unit prices greater than 210 yuan / g). In addition, the method has a low drawing temperature, which reduces energy consumption and has low equipment requirements.

[0024] (4) The method for testing the ionic conductivity of ceramic electrolyte fiber of the present invention has few steps and is simple to operate. Attached Figure Description

[0025] Figure 1 DSC curves of the thermostretchable modified LAGP glasses prepared in Examples 1-5;

[0026] Figure 2 EIS images of ceramic electrolyte sheets prepared using the thermostretchable modified LAGP glass of Examples 1-5;

[0027] Figure 3 A photograph of the ceramic electrolyte fiber prepared in Example 4;

[0028] Figure 4 EIS spectrum image of the ceramic electrolyte fiber prepared in Example 4;

[0029] Figure 5 EIS spectrum of ceramic electrolyte fiber prepared in Example 4;

[0030] Figure 6 DSC curves of the thermostretchable modified LAGP glasses prepared in Examples 6-8;

[0031] Figure 7 EIS images of ceramic electrolyte sheets prepared using the thermostretchable modified LAGP glass of Examples 6-8;

[0032] Figure 8 Photographs showing the preparation of ceramic electrolyte fibers from the heat-stretchable modified LAGP glass of Example 6. Detailed Implementation

[0033] The present invention will be further described below with reference to the accompanying drawings and specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading this description, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0034] Example 1

[0035] A thermostretchable modified LAGP glass, with the structural formula: Li 1.5 Al 0.5 Ge 1.5 P3O 12 , denoted as LAGP.

[0036] The above-mentioned method for preparing thermostretchable modified LAGP glass is as follows: Weigh 9.8748 g of LiPO3, 9.1915 g of Al(PO3)3, and 10.9337 g of GeO2, grind and mix them for 30 min, and then add them to a corundum crucible. Place the crucible in a furnace at 1250℃ and melt it for 30 min until a homogeneous glass melt is formed. Then, cast it into a copper mold to form a shape, and then transfer it to a muffle furnace at 470℃ for annealing for 4 h. Finally, cool it to room temperature with the furnace to obtain thermostretchable modified LAGP glass.

[0037] A small amount of thermostretchable modified LAGP glass was ground into powder, and DSC was tested at a heating rate of 10℃ / min. The DSC curve is shown in [reference needed]. Figure 1 We obtained that its ΔT = 98℃.

[0038] The aforementioned thermostretchable modified LAGP glass was cut into 2mm thick glass sheets, then placed in a muffle furnace and heated to 600℃ at a rate of approximately 5℃ / min, held for 30min for nucleation, and then heated to 750℃ and held for 2h for crystallization. The resulting ceramic electrolyte sheet was polished, sputtered with gold, and then its room temperature EIS spectrum (e.g., EIS) was measured. Figure 2 Its ionic conductivity is calculated to be 1.05 × 10⁻⁶. -4 S / cm.

[0039] Example 2

[0040] A thermostretchable modified LAGP glass, with the structural formula: Li 1.5 Al 0.5 Ge 1.5 P3O 12 ·0.06Y2O3, denoted as LAGP+0.06Y2O3.

[0041] The above-mentioned method for preparing thermostretchable modified LAGP glass is as follows: Weigh 8.9633g of LiPO3, 9.1774g of Al(PO3)3, 10.9169g of GeO2 and 0.9423g of Y2O3, grind and mix them for 30 minutes, and then add them to a corundum crucible. Place the crucible in a furnace at 1300℃ and melt for 20 minutes to form a homogeneous glass melt. Then, cast it into a copper mold to form a shape, and then transfer it to a muffle furnace at 470℃ for annealing for 4 hours. Finally, cool it to room temperature at a rate of 2℃ / min to obtain thermostretchable modified LAGP glass.

[0042] The DSC curve of the thermostretchable modified LAGP glass prepared in Example 2 is shown in Figure 2. Figure 1 Therefore, we can conclude that its ΔT = 99℃.

[0043] The aforementioned thermostretchable modified LAGP glass was cut into 2 mm thick glass sheets, then placed in a muffle furnace and heated to 620 °C at a rate of approximately 5 °C / min, held for 30 min for nucleation, and then heated to 750 °C and held for 2 h for crystallization. The resulting electrolyte sheet was polished, sputtered with gold, and then its room temperature EIS spectrum (e.g., ESI) was measured. Figure 2 ), its ionic conductivity is calculated to be 2.57 × 10⁻⁶. -4 S / cm.

[0044] Example 3

[0045] A thermostretchable modified LAGP glass, with the structural formula: Li 1.5 Al 0.5 Ge 1.5 P3O 12 ·0.05B2O3, denoted as LAGP+0.05B2O3.

[0046] The above-mentioned method for preparing heat-stretchable modified LAGP glass is as follows: Weigh 9.5788g of LiPO3, 9.1603g of Al(PO3)3, 10.8966g of GeO2 and 0.3644g of H3BO3, grind and mix them for 30 minutes, and then add them to a corundum crucible. Place the crucible in a furnace at 1250℃ and melt it for 20 minutes until a homogeneous glass melt is formed. Then, cast it into a copper mold to form a shape, and then transfer it to a muffle furnace at 470℃ for annealing for 4 hours. Finally, cool it to room temperature at a rate of 2℃ / min to obtain the modified LAGP glass.

[0047] The DSC curve of the thermostretchable modified LAGP glass prepared in Example 3 is shown in Figure 3. Figure 1 We obtained that its ΔT = 126℃.

[0048] The aforementioned thermostretchable modified LAGP glass was cut into 2 mm thick glass sheets, which were then placed in a muffle furnace and heated to 600 °C at a rate of approximately 5 °C / min and held for 30 min to induce nucleation. The temperature was then increased to 750 °C and held for 2 h to induce crystallization. The resulting electrolyte sheet was polished, sputtered with gold, and then its room temperature EIS spectrum (e.g., ESI) was measured. Figure 2 Its ionic conductivity is calculated to be 2.86 × 10⁻⁶. -4 S / cm.

[0049] Example 4

[0050] A thermostretchable modified LAGP glass, with the structural formula: Li 1.5 Al 0.5 Ge 1.5 P3O 12 ·0.06Y2O3·0.05B2O3, denoted as LAGP+0.06Y2O3+0.05B2O3.

[0051] The above-mentioned method for preparing heat-stretchable modified LAGP glass is as follows: Weigh 8.8366g of LiPO3, 9.0477g of Al(PO3)3, 10.7627g of GeO2, 0.424g of H3BO3, and 0.929g of Y2O3, grind and mix them for 30 minutes, and then add them to a corundum crucible. Place the crucible in a furnace at 1250℃ and melt it for 30 minutes until a homogeneous glass melt is formed. Then, cast it into a copper mold to form a shape, and then transfer it to a muffle furnace at 470℃ for annealing for 4 hours. Finally, cool it to room temperature at a rate of 2℃ / min to obtain the modified LAGP glass.

[0052] The DSC curve of the thermostretchable modified LAGP glass prepared in Example 4 is shown in Figure 4. Figure 1 We obtained that its ΔT = 132℃.

[0053] The aforementioned thermostretchable modified LAGP glass was cut into 2 mm thick glass sheets, then placed in a muffle furnace and heated to 620 °C at a rate of approximately 5 °C / min, held for 30 min for nucleation, and then heated to 750 °C and held for 2 h for crystallization. The resulting electrolyte sheet was polished, sputtered with gold, and then its room temperature EIS spectrum (e.g., ESI) was measured. Figure 2 Its ionic conductivity is calculated to be 3.11 × 10⁻⁶. -4 S / cm.

[0054] Preparation method of ceramic electrolyte fiber: The above-mentioned heat-stretchable modified LAGP glass is processed into a preform by cutting, grinding and polishing. Then, it is placed in the drawing furnace of the optical fiber drawing tower and heated to 620°C at a rate of 5°C / min. The fiber is then hot-drawn to obtain the fiber. The obtained fiber is placed in an alumina ceramic boat and placed in a muffle furnace. The temperature is raised to 630°C at a rate of 5°C / min and held for 30 min. Then, the temperature is raised to 750°C and held for 120 min. After cooling, the ceramic electrolyte fiber is obtained.

[0055] Figure 3 The image shows the ceramic electrolyte fiber prepared in Example 4. It can be seen that the method of the present invention can be used to prepare ceramic electrolyte fibers by hot drawing.

[0056] The ionic conductivity of the ceramic electrolyte fiber prepared in Example 4 was tested: A 4mm long section of ceramic electrolyte fiber was taken, and both ends were adhered to conductive copper foil with conductive silver paste (e.g., ...). Figure 4 After drying, its EIS spectrum was measured using an electrochemical workstation (e.g., ...). Figure 5 Then, based on the end face area and effective length of the modified LAGP ceramic fiber, the ionic conductivity was calculated, and its room temperature ionic conductivity reached 3.87*10. -4 S / cm.

[0057] Example 5

[0058] A thermostretchable modified LAGP glass, with the structural formula: Li 1.5 Al 0.5 Ge 1.5 P3O 12 ·0.06La2O3·0.05B2O3, denoted as LAGP+0.06La2O3+0.05B2O3.

[0059] The above-mentioned method for preparing heat-stretchable modified LAGP glass is as follows: Weigh 8.717g of LiPO3, 8.9253g of Al(PO3)3, 10.617g of GeO2, 0.4182g of H3BO3, and 1.3224g of La2O3, grind and mix them for 30 minutes, and then add them to a corundum crucible. Place the crucible in a furnace at 1300℃ and melt it for 30 minutes until a homogeneous glass melt is formed. Then, cast it into a copper mold to form a shape, and then transfer it to a muffle furnace at 470℃ for annealing for 4 hours. Finally, cool it to room temperature at a rate of 2℃ / min to obtain the modified LAGP glass.

[0060] The DSC curve of the thermostretchable modified LAGP glass prepared in Example 5 is shown in Figure 5. Figure 1 We obtained that its ΔT = 134℃.

[0061] LAGP glass was cut into glass sheets approximately 2 mm thick, then placed in a muffle furnace and heated to 630 °C at a rate of about 5 °C / min, held for 30 min for nucleation, and then heated to 750 °C and held for 2 h for crystallization. The resulting electrolyte sheet was polished, sputtered with gold, and its room temperature EIS spectrum (e.g., EIS) was measured. Figure 2 Its ionic conductivity is calculated to be 2.97 × 10⁻⁶. -4 S / cm.

[0062] Example 6

[0063] A thermostretchable modified LAGP glass, with the structural formula: Li 1.8 Al 0.5 Ge 1.5 P 2.7 Si 0.3 O 12 , denoted as LAGSP.

[0064] The above-mentioned method for preparing heat-stretchable modified LAGP glass is as follows: Weigh 7.0477g of LiPO3, 1.97g of Li2CO3, 9.0201g of Al(PO3)3, 10.7298g of GeO2, and 1.2323g of SiO2, grind and mix them for 30 minutes, and then add them to an alumina crucible. Place the crucible in a furnace at 1250℃ and melt it for 30 minutes until a homogeneous glass melt is formed. Then, cast it into a copper mold to form a shape, and then transfer it to a muffle furnace at 450℃ for annealing for 5 hours. Finally, cool it to room temperature at a rate of 2℃ / min to obtain the modified LAGP glass.

[0065] The DSC curve of the thermostretchable modified LAGP glass prepared in Example 6 is shown in Figure 6. Figure 6 We obtained that its ΔT = 132℃.

[0066] LAGP glass was cut into glass sheets approximately 2 mm thick, then placed in a muffle furnace and heated to 600 °C at a rate of about 5 °C / min, held for 30 min for nucleation, and then heated to 720 °C and held for 2 h for crystallization. The resulting electrolyte sheet was polished, sputtered with gold, and its room temperature EIS spectrum (e.g., EIS) was measured. Figure 7 ), its ionic conductivity is calculated to be 2.19 × 10⁻⁶. -4 S / cm.

[0067] Preparation method of ceramic electrolyte fiber: The above-mentioned heat-stretchable modified LAGP glass is processed into a preform by cutting, grinding and polishing. Then, it is placed in the drawing furnace of the optical fiber drawing tower and heated to 580°C at a rate of 5°C / min. The fiber is then hot-drawn to obtain the fiber. The obtained fiber is placed in an alumina ceramic boat and placed in a muffle furnace. The temperature is raised to about 620°C at a rate of 5°C / min and held for 30 min. Then, the temperature is raised to 750°C and held for 120 min. After cooling, the ceramic electrolyte fiber is obtained.

[0068] Figure 8 The photograph shows the process of drawing ceramic electrolyte fibers from the heat-stretchable modified LAGP glass of Example 6. As can be seen, the modified LAGP glass in this example can be drawn into modified LAGP fibers by heating it to 580°C.

[0069] Example 7

[0070] A thermostretchable modified LAGP glass, with the structural formula: Li 1.8 Al 0.5 Ge 1.5 P 2.7 Si 0.3 O 12 ·0.06Y2O3, denoted as LAGSP+0.06Y2O3.

[0071] The above-mentioned method for preparing heat-stretchable modified LAGP glass is as follows: Weigh 6.8367g of LiPO3, 1.911g of Li2CO3, 8.75g of Al(PO3)3, 10.4085g of GeO2, 1.1954g of SiO2, and 0.8985g of Y2O3, grind and mix them for 30 minutes, and then add them to a corundum crucible. Place the crucible in a furnace at 1250℃ and melt it for 30 minutes until a homogeneous glass melt is formed. Then, cast it into a copper mold to form a shape, and then transfer it to a muffle furnace at 450℃ for annealing for 5 hours. Finally, cool it to room temperature at a rate of 2℃ / min to obtain the modified LAGP glass.

[0072] The DSC curve of the thermostretchable modified LAGP glass prepared in Example 7 is shown in Figure 7. Figure 6 We obtained that its ΔT = 132℃.

[0073] LAGP glass was cut into glass sheets approximately 2 mm thick, then placed in a muffle furnace and heated to 600 °C at a rate of about 5 °C / min, held for 30 min for nucleation, and then heated to 720 °C and held for 2 h for crystallization. The resulting electrolyte sheet was polished, sputtered with gold, and its room temperature EIS spectrum (e.g., EIS) was measured. Figure 7 Its ionic conductivity is calculated to be 1.92 × 10⁻⁶. -4 S / cm.

[0074] Example 8

[0075] A thermostretchable modified LAGP glass, with the structural formula: Li 1.8 Al 0.5 Ge 1.5 P 2.7 Si 0.3 O 12 ·0.06Y2O3·0.05B2O3, denoted as LAGSP+0.06Y2O3+0.05B2O3.

[0076] The above-mentioned method for preparing heat-stretchable modified LAGP glass is as follows: Weigh 6.7903g of LiPO3, 1.898g of Li2CO3, 8.6906g of Al(PO3)3, 10.3378g of GeO2, 1.1873g of SiO2, 0.2036g of H3BO3, and 0.8924g of Y2O3, grind and mix them for 30 minutes, and then add them to a corundum crucible. Place the crucible in a furnace at 1250℃ and melt it for 30 minutes until a homogeneous glass melt is formed. Then, cast it into a copper mold to form a shape, and then transfer it to a muffle furnace at 450℃ for annealing for 5 hours. Finally, cool it to room temperature at a rate of 2℃ / min to obtain the modified LAGP glass.

[0077] The DSC curve of the thermostretchable modified LAGP glass prepared in Example 8 is shown in Figure 8. Figure 6We obtained that its ΔT = 126℃.

[0078] LAGP glass was cut into glass sheets approximately 2 mm thick, then placed in a muffle furnace and heated to 600 °C at a rate of about 5 °C / min, held for 30 min for nucleation, and then heated to 720 °C and held for 2 h for crystallization. The resulting electrolyte sheet was polished, sputtered with gold, and its room temperature EIS spectrum (e.g., EIS) was measured. Figure 7 ), its ionic conductivity is calculated to be 2.06 × 10⁻⁶. -4 S / cm.

[0079] The above description, in conjunction with specific preferred embodiments, provides a further detailed explanation of the present invention. It should not be construed that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art, various simple deductions or substitutions can be made without departing from the concept of the present invention, and all such modifications and substitutions should be considered within the scope of protection of the present invention.

Claims

1. A thermostretchable modified LAGP glass, characterized in that, It has the following general structural formula: Li 1.5+x Al 0.5 Ge 1.5 Q 3-x Si x O 12 ·yM·zN, Wherein, M is selected from one or more of Y2O3, La2O3, Gd2O3, Nd2O3, Lu2O3, Yb2O3, Eu2O3, Tm2O3, Er2O3, Dy2O3, Ho2O3, Sm2O3, CeO2, and Tb4O7; N is a flux, which is B2O3; The values ​​of x, y, and z are in the range of 0.2≤x≤0.4, 0.06≤y≤0.08, and 0.03≤z≤0.

08.

2. The method for preparing the thermostretchable modified LAGP glass according to claim 1, characterized in that, According to the proportions in the general formula of claim 1, weigh out lithium source, aluminum source, phosphorus source, GeO2, SiO2, rare earth oxide, and flux, and mix them evenly. Place the resulting mixture in a furnace at 1200~1300℃ and melt it for 10~60 min to obtain glass liquid. Then, cast the glass liquid into a mold to form it. After annealing, cool it to room temperature to obtain heat-stretchable modified LAGP glass.

3. The method for preparing thermostretchable modified LAGP glass as described in claim 2, characterized in that, The lithium source is at least one of Li2CO3, LiNO3, and LiPO3; the phosphorus source is at least one of P2O5, NH4H2PO4, (NH4)2HPO4, and LiPO3; and the aluminum source is at least one of Al2O3 and Al(PO3)3.

4. The method for preparing thermostretchable modified LAGP glass as described in claim 2 or 3, characterized in that, The annealing temperature is 400~500℃, and the time is 2~12 h.

5. A method for preparing ceramic electrolyte fibers, characterized in that, The heat-stretchable modified LAGP glass described in claim 1 is processed into preforms with a diameter of 2-20 mm through cutting, grinding, and polishing processes. These preforms are then placed in the drawing furnace of an optical fiber drawing tower and heated at a rate of 2-5 °C / min to 100-120 °C above the glass transition temperature Tg. The fiber diameter is controlled by adjusting the feeding and winding speeds of the drawing tower. Fibers are obtained through hot drawing. The obtained fibers are then heated at a rate of 2-5 °C / min to the crystallization temperature Tc ± 20 °C and held for 10-120 min. The temperature is then raised to 700-850 °C and held for 30-120 min to obtain ceramic electrolyte fibers.

6. The method for preparing ceramic electrolyte fibers as described in claim 5, characterized in that, The fiber diameter is 50~1000μm.

Citation Information

Patent Citations

  • All-solid-state composite electrolyte based on glass fiber vertical array structure and preparation method thereof

    CN111653823A

  • Lithium secondary battery and electrode for lithium secondary battery

    US20080268348A1